2021
DOI: 10.1158/1538-7445.am2021-1883
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1883: Mechanism of action and biomarker strategy for HFB200301, an anti-TNFR2 agonist antibody for the treatment of cancer

Abstract: Despite the success of immune check point inhibition, identification of other pathways capable of modulating the immune response against the tumor remains challenging. T-cell co-stimulation has been investigated with limited clinical success so far due in part to the fine tuning required for agonist antibodies against those co-stimulatory receptors and to the lack of biomarkers to facilitate the selection of patients likely to benefit from T-cell co-stimulation. TNFR2 belongs to the TNFR family of costimulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Using human TNFR2 knock-in mouse models, it was suggested that HFB200301 could stimulate anti-tumor responses through expansion of effector T cells and NK cells without depleting the Tregs. The agonistic ability of the antibody was found to be independent of FcγR mediated cross-linking ( 146 ). Although much of the data is not yet mature, with peer review lacking for most of the pre-clinical studies, the potential of TNFR2 targeting antibodies in oncology are exciting and the initial results from clinical trials are eagerly awaited by the immuno-oncology community.…”
Section: Targeting Tnfr2mentioning
confidence: 99%
“…Using human TNFR2 knock-in mouse models, it was suggested that HFB200301 could stimulate anti-tumor responses through expansion of effector T cells and NK cells without depleting the Tregs. The agonistic ability of the antibody was found to be independent of FcγR mediated cross-linking ( 146 ). Although much of the data is not yet mature, with peer review lacking for most of the pre-clinical studies, the potential of TNFR2 targeting antibodies in oncology are exciting and the initial results from clinical trials are eagerly awaited by the immuno-oncology community.…”
Section: Targeting Tnfr2mentioning
confidence: 99%
“…This effect of TNFR2 agonism has shown to be pathological-relevant, as TNFR2 is expressed by tumor-infiltrating Tcon cells ( 89 , 91 93 ) and proinflammatory subsets of CD4 Tcon cells ( 94 , 95 ), suggesting that TNFR2 agonists could induce the activation of TNFR2 signal in Tcon cells in tumor and inflammatory diseases. In the mouse tumor model, it was reported that TNFR2 agonistic antibodies induced the expansion of CD4 + Tcon cells without affecting the Treg number in vivo ( 58 ). Therefore, Tcon cells are also a potential target of TNFR2 agonists albeit with relatively lower TNFR2 expression.…”
Section: Tnfr2 Agonist-induced Activation Of Effector Immune Cellsmentioning
confidence: 99%
“…The antitumor effect of TNFR2-targetingantibody (Y9) can be impaired by the depletion of NK cells, suggesting that TNFR2 agonists may also target the NK cells to elicit antitumor immune responses ( 54 ). Now several TNFR2-stimulating antibodies in clinical development have been reported to enhance NK cell activation ( 58 , 73 ). However, the mechanism that how TNFR2 agonism affects tumor-infiltrating NK cells remains to be investigated.…”
Section: Tnfr2 Agonist-induced Activation Of Effector Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…HFB200301 is a first-in-class agonistic anti-TNFR2 agonist antibody that binds potently and selectively to TNFR2, which demonstrates potent antitumor activity alone and in combination with anti-PD-1. HFB200301 activates CD4+, CD8+ T cells, and NK cells in vitro and induces expansion of CD4+ and CD8+ T cells and NK cells in the TME without affecting regulatory T cells numbers in vivo ( 64 ). Another TNFR2 agonist antibody is MM-401, which shows T-cell co-stimulation and robust antitumor activity and immune memory in a mouse.…”
Section: Targeting Tnfr2: Blocking and Activating Drugs Under Clinica...mentioning
confidence: 99%